Emancipation from What and for Whom? A Materialist Critique of Recognition - Cicerchia, Lillian (Itinerari, 2023)
This paper makes a materialist critique of Axel Honneth’s theory of recognition. It explores Honneth’s relationship to Marxism as a foil for developing his Hegelian-informed, pragmatist way of thinking about human emancipation as a struggle for recognition, as well as the role of critical theory in that struggle. The paper then argues that this “Marxian foil” distorts the issue of emancipation from and relative to structural injustices, which leads recognition theory to equivocate on the kind of emancipatory knowledge that critical theory seeks to produce. Finally, it argues that contemporary iterations of historical materialism are congenial to many of pragmatism’s insights. It also has a normative horizon that the recognition paradigm does not – namely, thematizing the problem of constraints on self-determination in broader struggles for emancipation, and indeed, recognition.